The usefulness of financial statement reporting by charitable companies limited by guarantee in Malaysia / Ahmad Saiful Azlin Puteh Salin, Muhammad Faiz Tumiran and Anuar Nawawi. - Puteh Salin, Ahmad Saiful Azlin; Tumiran, Muhammad Faiz; Nawawi, Anuar (Universiti Teknologi MARA Cawangan Selangor, 2017)
The purpose of this study is primarily to scrutinize the usefulness of financial statement reporting by charitable companies limited by guarantee in Malaysia as prescribed in the rules and regulations. The main concern is whether there is limitation for the charitable company to follow this requirement in which, its performance and accountability will be analyzed. These attributions will lead to the improvement on the level of governance and accountability to satisfy all the relevant parties, especially the stakeholders and public interest. 50 companies were selected as a sample and three years of financial reports from 2009 to 2011 were scrutinized. Descriptive analysis was used to analyse the data. This study found that the majority of the charitable companies adopted PERS (Private Entity Reporting Standard) and FRS (Financial Reporting Standard) in preparing their financial report while less than 5 percent did not clearly state their accounting standard. For the establishment objective, at least half of the companies spent more than 50 percent contribution received for their institution. This study also found that more than 80 percent of the companies at least provided a minimum disclosure on the contributions received in their financial report with a moderate level quality of information. However, less than 50 percent of the companies fully complied with the basic requirement of the Companies Act 1965 and are being compounded by the regulators.